Analysis of Profitability Ratios and Solvency Ratios on Financial Performance at PT Bank Negara Indonesia Tbk Listed on the Indonesia Stock Exchange (BEI) 2018-2022 - Setiandi, Mohamad Fahry; Rokhaminawanti, Ersri (CV. Rayyan Dwi Bharata, 2024)
Financial performance is one of the important factors in assessing a company's success, especially for public companies. PT Bank Negara Indonesia Tbk is one of the registered banking companies in the Indonesia Stock Exchange and has significant financial performance in the capital market. This study aims to analyze the profitability ratios and solvency ratios on the financial performance of PT Bank Negara Indonesia Tbk that is listed on the Indonesia Stock Exchange (BEI) for the period of 2018-2022. The data used in this research are the financial statements of PT Bank Negara Indonesia Tbk for the same period. The analysis methods that are used in this study are quantitative analysis. The research findings show that the profitability ratios, consisting of Return on Assets (ROA), Profit Margin, and Return on Equity (ROE), have a positive and significant effect on the financial performance of PT Bank Negara Indonesia Tbk. Meanwhile, the solvency ratios, consisting of Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), and Interest Coverage Ratio (ICR), have a negative and significant effect on financial performance. Based on the results, it can be concluded that PT Bank Negara Indonesia Tbk needs to pay attention to the profitability ratios and solvency ratios in maintaining its good financial performance. In terms of this, the company needs to maximize the use of its assets to increase its profitability and reduce its dependency on debt financing sources to uphold its healthy solvency.